Advancements in managing chemotherapy-induced nausea and vomiting: From efficacy to cost-effectiveness - Yuvashree Chandrasekaran; Mukesh Kumar Dharmalingam Jothinathan (Oral Oncology Reports)
Chemotherapy-Induced Nausea and Vomiting (CINV) treatment prevails as a principal clinical problem in modern oncology, leading to poor quality of life of patients and a threat for compliance with treatment regimens. Electronic patient-reported outcomes are now proved to be the promising tool which determines and combats prolonged issues in Asia Pacific such as loss of appetite, nausea, and vomiting alongside other treatment-related issues. Such people might perceive CINV as a terrible threat they are battling with that is showing up in the form of nausea after chemotherapy and nausea which they are afraid of. Meanwhile, our real-life clinical practice is not at its optimal adherence to prevention guidelines. A personalized antiemetic prophylaxis that consists of intravenous medications, oral choices, extended-period dosing and radiation emesis prevention is necessary. Approaches like monthly olanzapine and ginger have shown to be cheaper and work in the prevention of CINV. A review of the available research indicates that there are specific kinds of treatment therapies that are effective as well as inexpensive such as netupitant and palonosetron combination therapy. With tropisetron along with dexamethasone acting as first choice for controlling CINV symptoms, especially though cisplatin, the superior CINV control is ensured for both acute and delayed symptoms. Palonosetron competently affords the acute and long-lasting phases of nausea. These evidence-based findings, therefore, highlight the significance of improving the anti-emetic treatments to allow patients derive maximum benefit and provide relief for the ones with treatment-related side effects in oncology management.